Analisis Potensi dan Perencanaan Agrowisata di Desa Ciliang, Pangandaran - Wahju, Ronny Irawan; Thoybah, Rezkino; Fahrizal, Muhammad Fayyadh; Alfarezi, Muhammad; Melawati, Lia; Putri, Clarisyah Karenia; Saelan, Yudithia; Khalila, Fithriana; Putra, Tito Dzullyardana (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
This activity aims to empower local potential to achieve sustainable agrotourism-based economic independence, creating agrotourism destinations managed in a participatory and inclusive manner by the community. Implementation methods include a participatory approach, mapping local potential, institutional mentoring, and the development of environmentally friendly agrotourism attractions and infrastructure. Results indicate increased community involvement in agrotourism management, the growth of community-based tourism awareness groups, and the establishment of educational agrotourism routes that integrate agriculture, local culture, and environmental conservation. Furthermore, this activity encourages the emergence of micro-enterprises based on local products that support the local economy. This activity demonstrates that a community-based approach and sustainability principles are effective in developing agrotourism destinations that not only improve economic well-being but also maintain environmental sustainability and strengthen local cultural identity.